Solar Powered Autonomous Vehicle for Seed Sowing - Ramesh, M. V.; Kumar, G. Vijay (New Approaches in Engineering Research Vol. 4, 2021)
In the agriculture industry, skilled labour is in short supply at the moment. Farmers must seek out cutting-edge technologies to carry out crop chores and increase yield. Rapid technological advancements have resulted in the creation of contemporary agricultural practices that employ creative technologies to tackle challenges connected with traditional approaches. The purpose of this paper is to describe the design and construction of a seed sowing vehicle that is controlled by a microcontroller and powered by a solar panel. The advantage with this seed sowing machine is that it can be programmed for any field conditions using microcontroller programming via PC or mobile, so as to make it perform the function autonomously.